2011
DOI: 10.1111/j.1939-1676.2011.0703.x
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study to Assess Tolerability of Early Enteral Nutrition via Esophagostomy Tube Feeding in Dogs with Severe Acute Pancreatitis

Abstract: Background: The putative role of the gut in amplification of systemic inflammation in acute pancreatitis is gaining credence, and intraluminal nutrition has been shown to decrease inflammation in experimental models of pancreatitis. Prepyloric feeding often is used in people with acute pancreatitis, but has not been evaluated in dogs.Hypothesis: Early intervention with enteral nutrition (EN) delivered proximal to the pylorus will be well tolerated in dogs with acute pancreatitis and provide justification for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 36 publications
0
34
0
5
Order By: Relevance
“…The urban location of this hospital may, in part, account for this difference in patient cohorts. Additionally, the preferential use of EN over PN in most pancreatitic patients in recent years may help explain the change in patients selected for PN administration . Polytrauma can result in a marked stress response and significant protein catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The urban location of this hospital may, in part, account for this difference in patient cohorts. Additionally, the preferential use of EN over PN in most pancreatitic patients in recent years may help explain the change in patients selected for PN administration . Polytrauma can result in a marked stress response and significant protein catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The ideal duration of fasting has not been identified in human or veterinary literature, and may likely be patient‐severity dependent if required at all. In fact, further imposed anorexia may be counterproductive to overall gastrointestinal health as avoidance of EN has been correlated to increased gut permeability, bacterial or endotoxin translocation, and immunosuppression . Additionally, the gut itself may either start or contribute to the systemic inflammatory response in AP …”
Section: Discussionmentioning
confidence: 99%
“…Although studies prospectively evaluating tolerance of enteral feeding in veterinary patients with AP are limited, there is growing evidence supporting the benefits of early EN in this population. A recent small pilot study of dogs with AP demonstrated no exacerbation in signs of pain or vomiting in the enterally fed group when compared to the parenterally fed group . However, there are no trials in veterinary medicine comparing early EN to the traditional therapy of nothing per os (NPO) in AP .…”
Section: Introductionmentioning
confidence: 99%
“…Mansfield et al (2011) verificaram que a NE por meio de esofagostomia, em cães portadores de pancreatite grave e que não estavam aptos a ingerir voluntariamente os nutrientes, resultou em menos complicações do que o uso da NP. Em humanos, o suporte nutricional enteral por meio de tubo de alimentação tem sido eficiente para pacientes disfágicos vítimas de acidente vascular cerebral (Kang et al, 2010).…”
Section: Sonda Esofágicaunclassified
“…Aos poucos o desenvolvimento de técnicas adequadas e os estudos metabólicos e nutricionais permitiram que esse meio de fornecimento de nutrientes, considerado tão utópico, se tornasse realidade PUBVET v.11, n.9, p.901-912, Set., 2017 (Dudrick, 2009). A NP é mais cara do que a NE e tem seu uso restrito ao ambiente hospitalar devido à necessidade da implantação de cateter colocado em condições assépticas (Chan, 2009 , Chan, 2009, Queau et al, 2011, Mansfield et al, 2011.…”
Section: Nutrição Parenteralunclassified